Analysis of the Implementation of BSI Mobile Services on Customer Satisfaction at BSI KCP Medan Pulo Brayan - Dhita Lutfiah; Ahmad Amin Dalimunte (Journal of Indonesian Management, 2022)
The Bank has taken advantage of the development of information technology in its banking services by launching mobile banking (m-banking). Bank BSI is one of the banks that provides mobile banking services to customers named BSI Mobile. This study aims to determine how much customer interest in using BSI Mobile and how the application of BSI Mobile to customer satisfaction. This research is a quantitative research, the data obtained in this study is primary data because it is obtained from the results of interviews with customers of BSI KCP Medan Pulo Brayan. BSI Mobile is one of the distribution channels used to access customer accounts via smartphones using the 3G/4G technology network and Wifi owned by Bank Syariah Indonesia, can be installed on the Playstore or Appstore. The features in BSI Mobile provided are Account Info, Transfer, Payment, Purchase, Islamic Services, Sharing-Ziswaf, e-mas, Favorites, Cash Withdrawal, Open Account, Top-Up eWallet, E-Commerce, Scheduled Transactions, Keyboards, and Financing. The application of the database provided by Bank Syariah Indonesia to customer transaction activities through BSI Mobile is one of Bank Syariah Indonesia's efforts to improve service and existence in the current economic situation.